Cadastro ambiental rural como instrumento de prevenção e controle do desmatamento em Minas Gerais - Fonseca, Gustavo Endrigo de Sá (2020)
On May 25th 2012, it was published the Federal Law 12.651, a Forest Code which, among other information, created the Rural Environmental Registry (CAR, Portuguese acronym), a national electronic platform for registering rural properties whose objective is to expand environmental control, monitoring and planning, culminating in the fight against illegal deforestation. In the present study, a temporal and comparative analysis of deforested areas, authorizations for deforestation and the registration of properties in the SICAR system were carried out with the objective of evaluating this instrument in the prevention and control of irregular deforestation in the Paracatu River Basin, in Minas Gerais. It was found that adherence to the instrument was delayed and despite the decrease in the area deforested annually between 2012 and 2018, most of it took place without authorization from the environmental agency, and the percentage of regular interventions also decreased over the analyzed period. Most of the irregular deforestation occurred in properties that were subsequently registered in CAR. As of 2015 the irregular deforestation were found in properties already registered, pointing out that the CAR instrument needs to be added to complementary public policies to achieve the fight against illegal deforestation.